Climate Clever Clovers: New Paradigm to Reduce the Environmental Footprint of Ruminants by Breeding Low Methanogenic Forages Utilizing Haplotype Variation - Kaur, Parwinder; Appels, Rudi; Bayer, Philipp E.; Keeble-Gagnere, Gabriel; Wang, Jiankang; Hirakawa, Hideki; Shirasawa, Kenta; Vercoe, Philip; Stefanova, Katia; Durmic, Zoey; Nichols, Phillip; Revell, Clinton; et al. (Frontiers in Plant Science, 2017)
Mitigating methane production by ruminants is a significant challenge to global livestock production. This research offers a new paradigm to reduce methane emissions from ruminants by breeding climate-clever clovers. We demonstrate wide genetic diversity for the trait methanogenic potential in Australia’s key pasture legume, subterranean clover (Trifolium subterraneum L.). In a bi-parental population the broadsense heritability in methanogenic potential was moderate (H2 = 0.4) and allelic variation in a region of Chr 8 accounted for 7.8% of phenotypic variation. In a genome-wide association study (GWAS) we identified four loci controlling methanogenic potential assessed by an in vitro fermentation system. Significantly, the discovery of a Single Nucleotide Polymorphism (SNP) on Chr 5 in a defined haplotype block with an upstream putative candidate gene from a plant peroxidase-like superfamily (TSub_g18548) and a downstream lectin receptor protein kinase (TSub_g18549) provides valuable candidates for an assay for this complex trait. In this way haplotype variation can be tracked to breed pastures with reduced methanogenic potential. Of the quantitative trait loci (QTL) candidates, the DNA-damage-repair/toleration DRT100-like protein (TSub_g26967), linked to avoid the severity of DNA damage induced by secondary metabolites, is considered central to enteric methane production, as are disease resistance (TSub_g26971, TSub_g26972 & TSub_g18549) and ribonuclease proteins (TSub_g26974, TSub_g26975). These proteins are good pointers to elucidate the genetic basis of in vitro microbial fermentability and enteric methanogenic potential in subterranean clover. The genes identified allow the design of a suite of markers for marker-assisted selection to reduce rumen methane emission in selected pasture legumes. We demonstrate the feasibility of a plant breeding approach without compromising animal productivity to mitigate enteric methane emissions, which is one of the most significant challenges to global livestock production.